PENGARUH PDB DAN KURS RUPIAH-USD TERHADAP INVESTASI PORTOFOLIO ASING DI INDONESIA - Kurdiansyah; Iwan Wisandani; Agus Ahmad Nasrulloh (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The influence of foreign investors on the financial sector in Indonesia is still very large. Therefore it is necessary to know the factors that affect the amount of Foreign Portfolio Investment in Indonesia. The aim of this study is to know the effect of the rupiah-usd exchange rate and GDP on Foreign Portfolio Investment in Indonesia in 2007Q1-2020Q4? The research method used is quantitative research. The data used is secondary data with documentation data collection techniques. The data analysis technique uses the Vectorautoregression (VAR) method with Eviews 9. The results of data analysis for the GDP variable (X1) only have a 0.4% effect on the fluctuation of Foreign Portfolio Investment (Y) in Indonesia and X1 does not have a Granger causality with Y.While the Rp-USD exchange rate (X2) has an effect of 7.78% on Fluctuations in Foreign Portfolio Investment (Y) and X1 have Granger causality with Y. And 91.8% of the variables that affect the fluctuation of Foreign Portfolio Investment are Foreign Portfolio Investment itself or other random variables. The conclusion of the study, GDP (X1) has an insignificant effect of 0.4% on Foreign Portfolio Investment in Indonesia (Y). The Rp-USD exchange rate (X2) has an effect of 7.78% on Foreign Portfolio Investment in Indonesia (Y).